Plastic film wrapped supers full of honey are frozen in an extraction facility as a sanitizing measure against Aethina tumida. Issue 2 (15th March 2017) - Mutinelli, Franco; La Mancusa, Francesco; Grasso, Marcello; Giuliano, Antonio; Gallina, Albino; Maroni Ponti, Andrea; Toson, Marica
Abstract : Following the discovery of the small hive beetle ( Aethina tumida ) (SHB) in the Calabria region of Italy in 2014, and similar finds in the region in the following years, it seems appropriate to evaluate measures that could allow the movement of supers full of honey from SHB non-infested but at risk areas, to extraction and processing facilities located in SHB non-infested areas. Freezing is appropriate as a sanitary measure for hive products such as pollen, but honey has a low thermal conductivity, so long periods of time are necessary to freeze whole supers. Supers containing two different honey crops (chestnut and eucalyptus) were placed in a freezing facility to determine the optimum times for SHB control. We found that supers full of honey should be stored in a −20 °C freezer for at least 71 (chestnut honey) and 83 (eucalyptus honey) hours respectively, to fulfil OIE recommendations for sanitization, but considering eucalyptus honey the worst scenario, we would recommend an 83-h-treatment generally.